PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Durima, Mahesha Elpan; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to examine partially and simultaneously the influence of Good Corporate Governance (GCG) and the disclosure of Corporate Social Responsibility (CSR) on the value of the company. Where the independent variable in this study is Good Corporate Governance (GCG) and the disclosure of Corporate Social Responsibility (CSR) while the dependent variable is the value of the company. The sample used is secondary data derived from the financial statements of the basic industrial and chemical companies of the chemical sub-sector listed on the Indonesia Stock Exchange (BEI) for the period 2010 to 2015.This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using simple and multiple linear regression analysis, t test, F test, and determination coefficient test with SPSS 20.The results of this study indicate that good corporate governance (GCG) variables partially (t test) affect the value of the company, while variable corporate social responsibility (CSR) partially (t test) does not affect the value of the company in the company Basic Industrial Sub Chemical and Sub Chemical Sector listed on the Indonesia Stock Exchange. The simultaneous test results (F) show the influence of good corporate governance (GCG) variables and the disclosure of corporate social responsibility (CSR) on the value of the company in the basic industrial and chemical sector of the chemical sub-sector listed on the Indonesia Stock Exchange.Keywords: Good Corporate Governance, Corporate Social Responsibility And Corporate Value